Entendre l’écriture pour écouter la sonorité. Lectures dans l’audibilité du lisible, entre Gaston Bachelard et Henri Bosco - Guillot, Matthieu (BACHELARD STUDIES - ÉTUDES BACHELARDIENNES - STUDI BACHELARDIANI, 2024)
Gaston Bachelard read and appreciated the stories of Henri Bosco a lot. Moreover, in their respective work we note a very close tone. The philosopher shares with the writer a propensity to examine the world of sounds within words. An avid reader of poets, Bachelard shows us how and why to listen to the poem. Bosco, for his part, is developing a whole poetic approach to listening that invites us to also focus on an auditory reading.